2011
DOI: 10.1002/msj.20243
|View full text |Cite
|
Sign up to set email alerts
|

Bed Rest in Pregnancy

Abstract: The use of bed rest in medicine dates back to Hippocrates, who first recommended bed rest as a restorative measure for pain. With the formalization of prenatal care in the early 1900s, maternal bed rest became a standard of care, especially toward the end of pregnancy. Antepartum bed rest is a common obstetric management tool, with up to 95% of obstetricians utilizing maternal activity restriction in some way in their practice. Bed rest is prescribed for a variety of complications of pregnancy, from threatened… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 70 publications
0
28
0
1
Order By: Relevance
“…Some women in this study were put on bed rest. While some studies suggest this might help control BP, there are no data to support the benefit of bed rest in prolonging gestation (41).…”
Section: Discussionmentioning
confidence: 99%
“…Some women in this study were put on bed rest. While some studies suggest this might help control BP, there are no data to support the benefit of bed rest in prolonging gestation (41).…”
Section: Discussionmentioning
confidence: 99%
“…Bed rest is a very common obstetrical management to restrict maternal activity even though there is minimal evidence that it decreases the risk of preterm delivery (Maloni, 2010). In addition Bigelow and Stone (2011) reviewed existing studies and found that there are no complications of pregnancy for which bed rest is consistently shown to be a beneficial intervention. A lack of objective research and randomised controlled trials analysing bed rest for a variety of complications of pregnancy is a major reason why up to 95% of obstetricians prescribe bed rest in their daily practice (Sciscione, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The hospital environment has also been shown to lead to depression (Thakur and Blazer, 2008). Many women contribute a substantial portion of the family income and multiple studies have shown that prolonged hospitalisation puts the majority of families under some degree of financial strain (Bigelow and Stone, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…2,9 In addition to the lack of demonstrable benefit, they highlight the potential harms, including venous thrombosis, bone demineralization, muscle atrophy, maternal weight loss, and maternal psychological problems.…”
Section: Other Reviews: Highlighting the Harmsmentioning
confidence: 98%
“…Ironically, most specialists reported that they expected little to no benefit from the intervention. 2 Because of this continuing paradox, we will summarize the relevant literature, consider the explanations for the persistence of bed rest, and describe the ethical implications of its continued use.…”
mentioning
confidence: 99%